Therapeutic effects of hysterosalpingography contrast media in infertile women: what do we know about the H2O in the H2Oil trial and why does it matter?. Issue 3 (16th December 2020) - Peart, Jane M; Sim, Robert G; Hofman, Paul L
ABSTRACT: Recent interest in the use of oil-soluble contrast media (OSCM) for hysterosalpingography (HSG) and other tubal flushing procedures is largely the result of publication of the large, multicentre, randomized controlled H2Oil trial in the New England Journal of Medicine in 2017, addressing the long-held suspicion that pregnancy rates following HSG with OSCM are higher than if a water-soluble contrast media (WSCM) is used. However, the findings of this trial have been compromised by the WSCM selected for comparison with OSCM. The chosen WSCM belongs to a superceded class of ionic media, with an iodine concentration, osmolality and viscosity all lying at the extreme end of the range for water-soluble radiographic contrast. The requirement for safe, cheap, versatile WSCM for intravascular use during computerized tomography, angiography and interventional procedures has resulted in considerable refinement of WSCM, with current widespread use of non-ionic, low osmolality or iso-osmolar WSCM in radiology, including for HSG. However, the use of the earlier ionic, high osmolality agents such as that selected for the H2Oil trial persists for HSG in some centres, despite potential adverse effects on the endometrium and fallopian tubal epithelium compared with more modern, less toxic WSCM. Knowledge of the variety of physical and chemical characteristics of the available WSCM is essential for interpretation of the current literature and establishing the most effective and safe water-soluble agent to use for HSG. Design of future clinical trials to establish the potential superiority of OSCM over WSCM for fertility enhancement must include the use of the readily available, inexpensive modern WSCM. While the fertility rates following OSCM HSG have been shown to be high in women with idiopathic infertility, more robust trials are required before the widespread use of OSCM for HSG or other modalities such as ultrasound and laparoscopy should be adopted.